The evolution of carbon-polluted white dwarfs at low effective temperatures. Issue 3 (18th October 2019) - Blouin, Simon; Dufour, Patrick
ABSTRACT: Taking advantage of the Gaia Data Release 2, recent studies have revisited the evolution of carbon-polluted white dwarfs (DQs) across a large range of effective temperatures. These analyses have clearly confirmed the existence of two distinct DQ evolutionary sequences: one with normal-mass white dwarfs and one with heavily polluted and generally more massive objects. The first sequence is thought to result from the dredge-up of carbon from the core, while the second could at least partially be made of descendants of hot DQs. However, the evolution of carbon-polluted white dwarfs below 6500 K remains unexplored, mainly due to the theoretical difficulties associated with modelling their dense atmospheres. In this work, we present a detailed star-by-star analysis of cool carbon-polluted white dwarfs. Our recently improved atmosphere models allow us to obtain good fits to most objects, including very cool DQpec white dwarfs with strongly shifted C2 molecular bands. We show that cool carbon-polluted white dwarfs keep following the two distinct evolutionary tracks previously identified at higher temperatures. We also find that most DQ white dwarfs transform into DQpec when their photospheric densities exceed ${≈}0.15\, {\textrm{g\, cm}}^{-3}$ . However, we identify stars for which the DQ→DQpec transition occurs at lower photospheric densities, possibly due to the presence of a strong magnetic field.